PHYSIOTHERAPY AS A TREATMENT FOR POST-PROSTATECTOMY URINARY INCONTINENCE, SYSTEMATIC REVIEW - TELLO MORENO, MÓNICA CRISTINA; CHACÓN, LISBETH JOSEFINA REALES; BONILLA AYALA, JOSSELYN GABRIELA; MEJÍA ORTÍZ, FÁTIMA PAMELA (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Introduction: In this systematic review, we will analyze physiotherapy as a treatment for post-prostatectomy urinary incontinence, to provide a clear vision of how this discipline can help in this problem, given that it is a frequent sequelae in men after surgery, which alters significantly the quality of life. Methods: A search for experimental studies was carried out in the PubMed, ScienceDirect, Scielo and Scopus databases. After applying the inclusion and exclusion criteria, 12 articles that focused on physiotherapy treatment for post-prostatectomy urinary incontinence were selected, and data were then extracted for review. Results: The selected articles cover various training techniques for the pelvic floor muscles with a significant impact on urinary continence. This exercise, added to other treatments such as acupuncture, feedback and global training with the diaphragm and abdomen, enhance its effectiveness. These results were reflected in the reduction in the use of urinary protectors and the improvement in quality of life. In addition, time is a crucial factor to achieve continence; studies show effectiveness the longer the training is performed and whether it is performed before and after surgery. Conclusion: There is scientific evidence that demonstrates that pelvic floor muscle training exercises as a physiotherapy treatment performed before and after radical prostatectomy allows the recovery of continence, improves quality of life and reduces the use of diapers.